Recycling of residuals of chlorinecontained pesticides - Prokopchuk, S. P.; Petruk, R. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
New technological scheme of recycling of residuals of chlorinecontained pesticides is offered which comprises the following stages: removal of chlorine from organic compound, which is the base of pesticide preparation. It is recommended before the beginning of recycling to determine by means of physical-chemical methods of the analysis the type of organic compound, which is the basis of pesticide preparation and presence of chlorine in order to select the optimum technological method of pesticides recycling. It is will enable to recycle the residuals of chlorinecontained pesticides and prevent the emission in the atmosphere of toxic substances.